2010
DOI: 10.1098/rsta.2009.0272
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, structures and properties of primarily nanosized homo/heterometallic palladium CO/PR 3 -ligated clusters

Abstract: Syntheses, properties and structures of nanosized palladium CO/PR 3 -ligated homoand heterometallic clusters containing up to 165 metal atoms are the focus of this review. The work discussed is primarily that of the authors and their coworkers. We propose that the unparalleled variety of structural types and the distinctive reactivities of neutral Pd n (CO) x (PR 3 ) y clusters composed of zerovalent Pd atoms are a consequence of relatively weak Pd-L(ligand) and Pd(0)-Pd(0) interactions that result from the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 53 publications
(78 reference statements)
2
72
0
Order By: Relevance
“…Clusters of aluminium appear to be a benign case for DFT treatments with the functional BP86, and there are no serious discrepancies with experiments. Mednikov & Dahl (2010) have prepared and structurally characterized an entire family of ligand-stabilized clusters of palladium, a work reviewed in this Theme Issue. The ligands, CO and/or PR 3 , neither oxidize nor reduce the Pd cluster core and should have a limited influence on its electronic structure.…”
Section: Clusters Of Aluminiummentioning
confidence: 99%
“…Clusters of aluminium appear to be a benign case for DFT treatments with the functional BP86, and there are no serious discrepancies with experiments. Mednikov & Dahl (2010) have prepared and structurally characterized an entire family of ligand-stabilized clusters of palladium, a work reviewed in this Theme Issue. The ligands, CO and/or PR 3 , neither oxidize nor reduce the Pd cluster core and should have a limited influence on its electronic structure.…”
Section: Clusters Of Aluminiummentioning
confidence: 99%
“…An increase in K value by 1 is accompanied by a decrease in the number of nuclear skeletal elements by 1. What was also found to be exciting is the discovery that the series method predicts that the clusters Pt 38 (CO) 44 2 (Mednikov and Dahl, 2010). The series method can also be useful in rapid categorization of the products encountered in EDESI-MS work (Bucher, 2003).…”
Section: Blackholes In the Nucleus And Ghost Skeletal Elementsmentioning
confidence: 99%
“…(Mednikov and Dahl, 2010). The former is described to have a Pd 19 pseudo octahedral while the latter has a Pd 15 kernel hexa-capped cubic with 8 capping Pd elements.…”
Section: Blackholes In the Nucleus And Ghost Skeletal Elementsmentioning
confidence: 99%
“…A good number of metal carbonyls and other related metal complexes have been applied in a good number of major industrial processes such as oxo-process, Monsanto process, Wacker oxidation process and Wilkinson catalyst in hydrogenation processes (Roth,1975;Ojima, et al, 2000;Grubbs, et al,2012;Wilkinson, et al, 1965;Tolman,1972). Many more carbonyl complexes of higher nuclearity skeletal metal atoms were synthesized (Dahl, et al, 2010). With emergency of borane chemistry (Stock, 1933;Longuet-Higgins , 1943;Lipscomb, 1963;Mingos, 1972;Lipscomb, 1976;Wade, 1976, Rudolph, 1976Hoffmann, 1982;Mingos, 1984;King, 1986;Greenwood and Earnshaw,1998;Shriver and Atkins, 1999;2002;2003;Balakrishnarajan and Hoffmann, 2004;Jemmis, 2005;Housecroft and Sharpe, 2005;Jemmis, et al, 2008;Welch, 2013), it was found that the structures of carbonyl clusters could be explained using Polyhedral Skeletal Electron Pair Theory (PSEPT) or Wade-Mingos rules (Wade, 1971;Mingos, 1972).…”
Section: Introductionmentioning
confidence: 99%